2015
DOI: 10.1155/2015/218253
|View full text |Cite
|
Sign up to set email alerts
|

Patients with MAC Lung Disease Have a Low Visceral Fat Area and Low Nutrient Intake

Abstract: Objective. This study aimed to examine the nutritional status and nutrient intake of patients with MAC lung disease with a focus on visceral fat area. Patients and Methods. Among 116 patients of our hospital with nontuberculous mycobacteriosis who were registered between May 2010 and August 2011, 103 patients with MAC lung disease were included in this study. In all patients, nutritional status and nutrient intake were prospectively examined. Results. Patients were 23 men and 80 women (mean age, 72.3 ± 10.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Several previous studies have assessed nutritional status in patients with PNTM disease (5,6). The BMI of patients with PNTM disease was lower than that of age-, sex-and race-matched controls or uninfected healthy controls in previous studies (4,23,24).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several previous studies have assessed nutritional status in patients with PNTM disease (5,6). The BMI of patients with PNTM disease was lower than that of age-, sex-and race-matched controls or uninfected healthy controls in previous studies (4,23,24).…”
Section: Discussionmentioning
confidence: 86%
“…Gatfield et al demonstrated that murine macrophages depleted of cholesterol had a reduced capacity (5). Another possibility is that the disease progression may result in reduced cholesterol despite adequate nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low BMI was associated with PNTM and was a predictor of dissemination [159]. PNTM has also been associated with low visceral fat and low nutrient intake [160]. Low BMI and cholesterol levels were predictors of bad prognosis in another study [161].…”
Section: (G) Malnutritionmentioning
confidence: 84%
“…• HIV [110][111][112][113][114][115][116][117][118][119] • Autoimmune diseases [120] • Cancer [121][122][123] • Immunosuppressive drugs [124][125][126][127][128][129] • Surgery [130][131][132][133] o Transplantation [134][135][136][137][138] • Age over 60 years old/Immunosenescence [139][140][141][142][143][144][145][146][147][148][149][150][151] • Malnutrition [152][153][154][155][156][157][158][159]…”
Section: (B) Cystic Fibrosisunclassified